(3NWHI GdhOGYs - (3Jbj GdOjf YHO Gddg Hf eMeO Hf CHj GdfLes
(3ChdgG (B:s
(3CNHQfG GdbGVi GdCLd GdChMO GdYGde Jbi GdOjf YHO Gddg Hf eMeO GHf CHj GdfLe abGd CjgG GdfGS CUeJhG hChSYhG def Ndace , abGd QLd jG QShd Gddg s
(3BNQgG (B:s
(3EdG hGf Gddg YR hLd eSGFdce Yf CYeGdce hGdSdGe Ydjce JeJ GdNWI hGdMeO ddg hMOg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH(B12s
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK , JQeje s
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHI GdLGeY GdcHjQ HUfYGA (B((3eLGejY (B87) s
Keywords: (3GdMOjK h GdeUWdMs